DICER1 syndrome: Approach to testing and management at a large pediatric tertiary care center. Issue 1 (27th September 2017) - van Engelen, Kalene; Villani, Anita; Wasserman, Jonathan D.; Aronoff, Laura; Greer, Mary‐Louise C.; Tijerin Bueno, Marta; Gallinger, Bailey; Kim, Raymond H.; Grant, Ronald; Meyn, M. Stephen; Malkin, David; Druker, Harriet
Abstract: Background: To expand the current knowledge of DICER1 syndrome and to propose criteria for genetic testing based on experience at a pediatric tertiary care center. Procedure: This study involved a retrospective chart review of the 78 patients (47 probands and 31 family members) seen in the Cancer Genetics Program at The Hospital for Sick Children (SickKids) who were offered genetic testing for DICER1 . Results: Of 47 probands offered genetic testing for DICER1, 46 pursued testing: 11 (23.9%) carried a pathogenic variant and one proband (2.1%) carried a missense variant of uncertain significance with evidence for pathogenicity. Thirty‐one family members of variant‐positive probands were offered testing: eight of the 25 who agreed to testing carried their familial variant (32.0%). Overall, 20 patients were identified to have a variant in DICER1 (eight males, 12 females). Of these, 13 (65.0%) presented with clinical manifestations associated with the syndrome. The most common lesions were pleuropulmonary blastoma (PPB) (five of 20 patients, 25.0%) and pineoblastoma (three of 20 patients, 15.0%). The average age at which individuals were diagnosed with a primary neoplasm was 5.2 years (range 0.8–20 years, median 3.0). Surveillance at our institution, with a median follow‐up time of 23 months, has identified PPB in two asymptomatic individuals. These lesions were identified at early stages, thus potentially reducing treatment‐related morbidity and mortality. Conclusion: This study further delineates the DICER1 syndrome phenotype and demonstrates the feasibility of a DICER1 syndrome surveillance protocol for the early detection of tumors.